Association of physical activity and physical performance with tibial cartilage volume and bone area in young adults. Issue 1 (December 2015) - Antony, Benny; Venn, Alison; Cicuttini, Flavia; March, Lyn; Blizzard, Leigh; Dwyer, Terence; Cross, Marita; Jones, Graeme; Ding, Changhai
Abstract Introduction Physical activity has been recommended to patients with knee osteoarthritis for improving their symptoms. However, it is still controversial if physical activity has effects on joint structures including cartilage volume. The aim of this study was to describe the associations between physical activity and performance measured 5 years prior and tibial cartilage volume and bone area in young adults. Methods Subjects broadly representative of the Australian population (n  = 328, aged 31–41 years, female 47.3 %) were selected from the Childhood Determinants of Adult Health study. They underwent T1-weighted fat-suppressed magnetic resonance imaging (MRI) scans of their knees. Tibial bone area and cartilage volume were measured from MRI. Physical activity (measured using long international physical activity questionnaire (IPAQ)) and performance measures (long jump, leg muscle strength, physical work capacity (PWC170 )) were measured 5 years prior. Results In multivariable analyses, total physical activity (min/week) (β: 0.30 mm3, 95 % CI: 0.13, 0.47), vigorous (β: 0.54 mm3, 95 % CI: 0.13, 0.94), moderate (β: 0.34 mm3, 95 % CI: 0.01, 0.67), walking (β: 0.40 mm3, 95 % CI: 0.07, 0.72) and IPAQ category (β: 182.9 mm3, 95 % CI: 51.8, 314.0) were positively associated with total tibial cartilage volume but not tibial bone area. PWC170, long jump and leg muscle strength were positively and significantly associated with both total tibial cartilage volume and total tibial bone area; and the associations with tibial cartilage volume decreased in magnitude but remained significant for PWC170 and long jump after further adjustment for tibial bone area. Conclusion While tibial bone area is affected only by physical performance, total tibial cartilage volume can be influenced by both physical activity and performance in younger adults. The clinical significance suggests a beneficial effect for cartilage but the bone area association was restricted to performance suggesting other factors rather than physical activity may be important.